ORGANOLEPTIC PROPERTIES OF KAPE-KAPE FISH (Psenes sp) USING EXTRACT OF KECOMBRANG FLOWER (Nicolaia Spesiosa, Horan) AS A NATURAL PRESERVATIVE - Christina Angelia Saragih; Lukman Hidayat; Tuti Tutuarima (Jurnal Agroindustri, 2019)
Freshness is one of the important factors in determining the quality of fish. Kecombrang flower extract contains active compounds of polyphenols, flavonoids, tannins and safonin as antimicrobial ingredients. Kecombrang flower extract can be used to slow down damage to fish. The study aimed to determine the effect of using kecombrang flower extract on organoleptic properties of fish (eyes, gills, mucus, meat, odor and texture). This study used a Completely Randomized Design (CRD) of one factor, namely the use of kecombrang flower extract with concentrations (0%, 2%, 4%, and 6%) and observation times of 0, 6, 12, 18 and 24 hours. All of data were analyzed using ANOVA test. At a concentration of 6% the 12th hour storage is still able to maintain the organoleptic properties of fish. Whereas at concentrations of 0%, 2% and 4% fish are no longer suitable for consumption.